COMPETITION AND WORK MOTIVATION OF EMPLOYEES OF PT. ASURANSI JIWA MANULIFE INDONESIA (MANULIFE INDONESIA) BRANCH OFFICE OF BANK DANAMON INDONESIA, TBK KOTA MATARAM - Ahmad Hulaimi; Nur Fitri Hidayanti (Bajang Institute, 2023)
Life insurance is a protection product that is not only beneficial for the policyholder, aka the insured, but also for the whole family. There are several benefits of life insurance that can be felt by families, including: 1) Guaranteeing the family's financial future, 2) Savings and reserve funds, 3) Inheritance for the family, 4) Reducing the burden on children when we retire. As the times progress, so many insurance companies have sprung up all over the world, and Indonesia is one of the countries with the most insurance companies providing various types of insurance products, one of which is life insurance, and the most well-known life insurance in Indonesia is Manulife Life Insurance. Indonesia.Manulife Indonesia Life Insurance is insurance that is trusted among the people of Indonesia, however, not a few people or customers of Manulife Indonesia Life Insurance are disappointed with the services provided. Therefore this research was conducted to find out more deeply what are the causes of Manulife Indonesia Life Insurance customer dissatisfaction with the services provided by the company. This study used a qualitative approach and observations were made from December 2022 to January 2023. The results of the research found in the field that employees in the marketing department were dishonest to potential customers or customers. So that in the future there will be inconvenience to customers which results in customer distrust of the company. Therefore, it is hoped that the Life Insurance company Manulife Indonesia will supervise every activity of its employees.